Proposal of a correction factor to measurements of hemoglobin by altitudinal tiers in 6-19 month old infants in Peru - Bartolo-Marchena, Marco (2017)
Introduction: Anemia is the largest nutritional problem in Peru. Objective: To determine changes in hemoglobin level according to altitude in Peruvian children in order to propose a national correction factor. Design: Descriptive, cross-sectional study. Setting: At national level. Participants: 22 500 children aged 6 to 59 months-old. Interventions: Data from the Demography and Family Health Survey (ENDES 2015) was used to select non-anemic children for the proposed formulation. An exponential regression model was used and the correction factor for hemoglobin (according to altitude) was: 8.3 *e (0,000426 * height) -12. Main outcome measure: Prevalence of anemia according to altitude. Results: The prevalence of anemia was compared according to the proposed correction factor versus the traditional formula used by the Center of Disease Control (CDC). The difference at national level reached 2.5%, being greater from 3 000 meters over sea level (9.2%). Regions with a difference over 5 percentage points were Junín (5,6%), Cusco (5,7%), Ayacucho (6%), Pasco (7,4%), Apurímac (7,8%), Huancavelica (9,9%), and Puno (12,7%). Conclusion: The proposed correction factor identifies lower prevalence of anemia compared to the traditional factor. This observation may be due to the differences found above 3 000 meters over the sea level.